Contrasting Winter Versus Summer Microbial Communities and Metabolic Functions in a Permafrost Thaw Lake - Vigneron, Adrien; Lovejoy, Connie; Cruaud, Perrine; Kalenitchenko, Dimitri; Culley, Alexander; Vincent, Warwick F. (Frontiers in Microbiology, 2019)
Permafrost thawing results in the formation of thermokarst lakes, which are biogeochemical hotspots in northern landscapes and strong emitters of greenhouse gases to the atmosphere. Most studies of thermokarst lakes have been in summer, despite the predominance of winter and ice-cover over much of the year, and the microbial ecology of these waters under ice remains poorly understood. Here we first compared the summer versus winter microbiomes of a subarctic thermokarst lake using DNA- and RNA-based 16S rRNA amplicon sequencing and qPCR. We then applied comparative metagenomics and used genomic bin reconstruction to compare the two seasons for changes in potential metabolic functions in the thermokarst lake microbiome. In summer, the microbial community was dominated by Actinobacteria and Betaproteobacteria, with phototrophic and aerobic pathways consistent with the utilization of labile and photodegraded substrates. The microbial community was strikingly different in winter, with dominance of methanogens, Planctomycetes, Chloroflexi and Deltaproteobacteria, along with various taxa of the Patescibacteria/Candidate Phyla Radiation (Parcubacteria, Microgenomates, Omnitrophica, Aminicenantes). The latter group was underestimated or absent in the amplicon survey, but accounted for about a third of the metagenomic reads. The winter lineages were associated with multiple reductive metabolic processes, fermentations and pathways for the mobilisation and degradation of complex organic matter, along with a strong potential for syntrophy or cross-feeding. The results imply that the summer community represents a transient stage of the annual cycle, and that carbon dioxide and methane production continue through the prolonged season of ice cover via a taxonomically distinct winter community and diverse mechanisms of permafrost carbon transformation.